Ireland : Fiscal Transparency Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses Ireland's Fiscal Transparency Assessment. The Irish government has ambitious plans to improve further the timeliness, quality, and comprehensiveness of its budgets, statistics, and accounts. Ireland has the capacity and information to bring its fiscal transparency practices into line with international best practice standards within a reasonable time frame, and at relatively modest additional cost. The Irish administration already incurs many of the fixed and ongoing costs associated with modern accrual-based accounting, and risk-based fiscal management. Fiscal reporting in Ireland is characterized by a high degree of disclosure but also a high degree of fragmentation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet